Effect of Mn content on the corrosion behavior and biocompatibility of biodegradable Zn-Mn alloys - Cheng, Xin; Lin, Qiuju; Jin, Hongxi; Han, Fufang; Dou, Xiaohui; Zhang, Xinwei; He, Zonghao; He, Chuan; Zhao, Songnan; Zhang, Dalei (Scientific reports, 2025)
Zinc-based alloys have attracted increasing attention as biodegradable metals by virtue of their excellent mechanical, degradable and biocompatible properties. By introducing different levels of manganese (0.1, 0.3, 0.5 and 0.8 wt